LKIAå¦æ ¡åˆä¸ä¸€å¹´çº§å¦ç”Ÿç¬”é¡ºåè¯¯åˆ†æžåŠæ•™å¦å¯¹ç– - SAFITRI, NUR (Universitas Tanjungpura, 2024)
The author conducted research on seventh-grade students at SMP LKIA Pontianak as the research subjects. This study aims to analyze the forms of errors in writing the stroke sequence